2016
DOI: 10.1021/jacs.6b08897
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Experimental and Computational Chemistry Reveals the Mechanism of Decomposition of Nickel–Ketene Complexes

Abstract: A series of (dppf)Ni(ketene) complexes were synthesized and fully characterized. In the solid state, the complexes possess η-(C,O) coordination of the ketene in an overall planar configuration. They display similar structure in solution, except in some cases, the η-(C,C) coordination mode is also detected. A combination of kinetic analysis and DFT calculations reveals the complexes undergo thermal decomposition by isomerization from η-(C,O) to η-(C,C) followed by scission of the C═C bond, which is usually rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…When ketene is added to an equimolar mixture of a substituted dppf ligand and Ni(COD) 2 , the formation of the Ni−ketene complex is observed as an appearance of two doublets in the 31 P NMR. X-ray crystal structures of the Ni−ketene complexes have shown that a square planar geometry exists around the nickel center, which, along with past Mayer bond analysis, 8 is indicative of a Ni(II) species. The two doublets seen in the 31 P NMR corresponds to the two inequivalent phosphine atoms on the complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When ketene is added to an equimolar mixture of a substituted dppf ligand and Ni(COD) 2 , the formation of the Ni−ketene complex is observed as an appearance of two doublets in the 31 P NMR. X-ray crystal structures of the Ni−ketene complexes have shown that a square planar geometry exists around the nickel center, which, along with past Mayer bond analysis, 8 is indicative of a Ni(II) species. The two doublets seen in the 31 P NMR corresponds to the two inequivalent phosphine atoms on the complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, the solid-state structure of 9d was previously found to be disordered, with random orientation of the ketene with respect to the nickel center. 8 In light of these, no discernible correlation between the bond lengths of the metallacycle and their observed rate constant of decomposition can be made. However, the observed electronic trend can be explained using past computational modeling of the decomposition pathway of the Ni−ketene complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations